FASILITAS PEMANFAATAN RUMPUT LAUT DI LAUT WULA, NUSA TENGGARA TIMUR - Stevie Stevie; Djidjin Wipranata (Jurusan Arsitektur dan Perencanaan, 2021)
East Nusa Tenggara is one of the provinces in Indonesia that has abundant marine natural wealth and is the second largest seaweed producer in Indonesia. Electricity is an important component in civilization and modernity, as well as the development of knowledge and information. However, East Nusa Tenggara often suffers from a shortage of electricity and fuel to carry out activities that are still dependent on fossil fuels that damage the environment. Therefore, realizing the enormous potential of the existing sea, it is necessary to build a facility for the use of seaweed that can be converted into biofuel, which can then be converted into electrical energy, and can also be processed into agar, carrageenan, and fertilizer focused on the Wula Village Sea as a source of energy. prime location. This project is also intended to educate visitors to get to know the sea more closely, as well as remind humans that in order to survive, we don't have to sacrifice other lives. This project uses a regenerative architecture design method that prioritizes the balance between humans, marine life, and the sea. This project consists of a program for the biofuel industry, electricity generation, tourism, seaweed raw material industry, workers' residences, and service rooms with futuristic building styles. Keywords: architecture; biofuel; electricity; futuristic; industry; seaweed; sea.AbstrakNusa Tenggara Timur merupakan salah satu provinsi di Indonesia yang memiliki kekayaan alam laut yang melimpah dan menjadi penghasil rumput laut terbesar kedua di Indonesia. Listrik merupakan komponen penting dalam peradaban dan modernitas, serta perkembangan pengetahuan dan informasi. Namun, seringkali Nusa Tenggara Timur mengalami kekurangan pasokan listrik dan bahan bakar untuk menjalankan aktivitas yang hingga saat ini masih bergantung dengan energi fosil yang merusak lingkungan. Maka dari itu, menyadari besarnya potensi laut yang ada, perlu dibangun suatu fasilitas pemanfaatan rumput laut yang dapat dikonversikan menjadi biofuel, yang selanjutnya dapat dikonversikan menjadi energi listrik, dan juga dapat diolah menjadi agar, karaginan, dan pupuk yang difokuskan pada Laut Desa Wula sebagai lokasi utama. Proyek ini juga dimaksudkan untuk memberikan edukasi kepada pengunjung untuk mengenal laut lebih dekat, serta mengingatkan manusia bahwa untuk bertahan hidup, kita tidak harus mengorbankan kehidupan lainnya. Proyek ini menggunakan metode desain regenerative architecture yang mengutamakan keseimbangan antara manusia, biota laut, dan laut. Proyek ini terdiri dari program industri biofuel, penghasil listrik, wisata, industri bahan baku rumput laut, tempat tinggal pekerja, dan ruang servis dengan gaya bangunan futuristik.